MEMBANGUN WEB PORTAL UNIVERSITAS SAINS DAN TEKNOLOGI JAYAPURA - Evanita Veronica Manullang; Marla Sheilamita Shalin Pieter (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2015)
University of Science and Technology Jayapura (USTJ) is a private universitylocated in the tip of eastern Indonesia precisely in Jayapura, capital city of Papua provinceand are under the coordinator Private Higher Education (KOPERTIS) Region XIV Papuaand West Papua. USTJ have 5 (five) Faculty, where between 5th faculty, there is onefaculties, namely the Faculty of Computer Science and Management (FIKOM) which is anexcellent faculty as a faculty with students and enthusiasts of most every year. As theFaculty generally teach about technology and the use of information technology devices,FIKOM website utilizes technology to create a web portal to help provide information tostudents per faculty. And in this study portal web creation, implementation on FIKOM is forstudents who is at the final level to be used in helping to get information about the titles offinal project (thesis) that has never existed as reference material.Web Portal was designed and built using the Waterfall method and based on the WirelessLocal Area Network (LAN). So that students of FIKOM that have a technology device withwifi facility and web browser applications can access the Web portal.